2018
DOI: 10.3390/e20050368
|View full text |Cite
|
Sign up to set email alerts
|

Writing, Proofreading and Editing in Information Theory

Abstract: Information is a physical entity amenable to be described by an abstract theory. The concepts associated with the creation and post-processing of the information have not, however, been mathematically established, despite being broadly used in many fields of knowledge. Here, inspired by how information is managed in biomolecular systems, we introduce writing, entailing any bit string generation, and revision, as comprising proofreading and editing, in information chains. Our formalism expands the thermodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Using the mutual information quantity, I − I (D) ≤ ∆U (D) − ∆U /T , which allows the information of the revised chain to be higher than that of the written chain (I > I (D) ) provided that the expected energy of the revised chain is lower than that of the written chain (∆U < ∆U (D) , necessary but not sufficient condition). Inequality ( 6) is reminiscent of an earlier result demonstrated independently 33 : by setting equal states for the written and revised chains, it is found that S − S (D) ≥ U −U (D) /T , which was used to formulate necessary and sufficient conditions for effective proofreading and editing in information theory 31 .…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Using the mutual information quantity, I − I (D) ≤ ∆U (D) − ∆U /T , which allows the information of the revised chain to be higher than that of the written chain (I > I (D) ) provided that the expected energy of the revised chain is lower than that of the written chain (∆U < ∆U (D) , necessary but not sufficient condition). Inequality ( 6) is reminiscent of an earlier result demonstrated independently 33 : by setting equal states for the written and revised chains, it is found that S − S (D) ≥ U −U (D) /T , which was used to formulate necessary and sufficient conditions for effective proofreading and editing in information theory 31 .…”
Section: Resultsmentioning
confidence: 81%
“…The chain has an associated reading direction, which is the one that makes the information along the chain meaningful (from left to right in Fig. 1), according to the language rules 31 . For example, a DNA template strand is copied (transcribed) from its 3' end to its 5' end during replication (transcription) and English language or sheet music are interpreted from left to right.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete memory effects have been considered in the study of spatial chains made up of physical subunits, including those with symbolic meaning, to access non-equilibrium dynamics [23] and information management in nanoscale systems [24]. They have also been taken into account to analyze abstract strings of symbols for the paradigm of communication [25]. However, full memory effects in temporal chains of events have never been treated from an exact perspective.…”
Section: Introductionmentioning
confidence: 99%